The Relevance of Akhlaqi Sufism to Economic Behavior: Thoughts of Shaykh Abdul Qodir Al-Jailani - Muhammad Arief Hidayat; Asyari Hasan (Universitas Muhammadiyah Magelang, 2021)
Sufism and economics are not the same thing. Sufism, according to popular belief, only teaches moral beliefs toward God and has nothing to do with the world, whereas economic behavior, on the other hand, is a worldly activity that has nothing to do with God. This is a huge oversight that humans are currently making, particularly in economic activities. As a result, the relevance of Sheikh Abdul Qodir Al-Sufism Jailani's thought to economic behavior is discussed in this study. This study will take a qualitative approach with a literature review. Sufism is very relevant to be applied and becomes a motive in economic activities, according to the findings of this study. The three concepts of Al-Jaelani, takhalli tahalli tajalli, will be the driving force of Islamic business ethics, directing good economic activities and bringing closer the concept of work as worship, for good in this world and hereafter.